The effect of sodium chloride (NaS1) concentration to corrosion rate - Nor Azmi , Badri (2012)
This thesis is carried out to investigate the effect of sodium chloride (NaCl) concentration to corrosion rate using electrochemical method and potentiodynamic. This study is about erosion and wear of material in corrosive environments. The corrosion test under erosion-corrosion condition were carried out by immersing the materials in the aqueous solution and combined erosion-corrosion effects were studied to observe the impact solid particle during the test. For this purpose, stainless steel has been tested under erosion-corrosion condition. This study was using three different concentration of NaCl as corrosive medium; 3.5 wt%, 10 wt% and 20 wt% and disturbance with 10 wt% sand particle. Increasing NaCl concentration promoted lower corrosion rate, pitting formation and small Ra value. Under the tested condition it was found that the higher concentration of NaCl led to a lower corrosion rate. The pitting formation was formed because of the impact of the sand particle but decreasing as concentration of NaCl increasing. The increasing concentration of NaCl leads to the decreasing of Ra value.